Investigation of A Potential Relationship Between Wild Bird Populations and Human Lyme Disease Rate in Connecticut from 1991-2002 - Al- Ali, Tamam (Journal of agricultural, environmental and veterinary sciences, 2017)
Lyme disease is the most common tick-borne disease in North America. Borrelia burgdorferi, is the pathogen, and the black-legged tick carries the bacteria and spreads it when feeding on the blood of animals and humans. At least 70 passerine species and one species of woodpecker in North American are parasitized by immature black-legged ticks. This hypothesis predicts that there would be a positive relationship between Lyme disease rates and bird numbers that infected with the pathogen, and there would be no relationship between Lyme disease rate and bird numbers that not known to be infected with the pathogen. I depended on the North American Breeding Bird Survey (BBS) to get bird species for 14 routes across Connecticut, and on the Connecticut DHS to get Lyme disease rates for the time period of the study (1991-2002). My bird data were: one group that included all 17 bird species that carry the pathogen, two species separately that are known to become infected by Lyme pathogen (American Robin and Gray Catbird), and a control species not known to carry the pathogen (American Redstart). I found significant positive relationships between bird numbers and human Lyme disease rate in two routes for the SCLP group, one route for American Robin, three routes for Gray Catbird, and two routes for American Redstart. Only Gray Catbird had a significant negative relationship with human Lyme disease rate in one route. Based on the positive relationships that appeared for American Redstart, the control species, and the few significant relationships for birds known to carry the pathogen, I reject the hypothesis that there is a strong relationship between numbers of birds that could be infected with B. burgdorferi and the rate of Lyme disease in people as measured by the methods used in this study.